Assessment of Erythrocytic Stress Response in Rathi Cattle from Rajasthan during Varying Ambiences - Joshi, Ashish; Kataria, Nalini; Asopa, Shesh; Kataria, Anil Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Assessment of erythrocytic stress response in Rathi cattle was done by determining non enzymatic biomarkers of oxidative stress, viz., vitamin A, vitamin C, vitamin E and glutathione in erythrocytes. For this purpose, blood samples were collected from apparently healthy Rathi female calves, heifers and cows from private dairies located in and around Bikaner district, Rajasthan during moderate, extreme hot, extreme cold and rainy ambiences to prepare lysates of erythrocytes. The overall mean values of erythrocytic vitamin A, vitamin C, vitamin E and glutathione were significantly (p≤0.05) lower during extreme cold, hot and rainy ambiences as compared to moderate ambience. The overall mean values of erythrocytic vitamin A, vitamin C, vitamin E and glutathione in cows were maximum and of calves were minimum (p≤0.05) in all the ambiences. In calves, calf yearling transition revealed maximum erythrocytic vitamin A, vitamin C, vitamin E and glutathione values, while in heifers category, post-pubertal heifers had significantly (p≤0.05) higher values of erythrocytic vitamin A, vitamin C, vitamin E and glutathione as compared to pre-pubertal in each ambience. In cows category, among group A animals, non-pregnant milch and in group B animals, multipara had significantly (p≤0.05) higher values of erythrocytic vitamin A, vitamin C, vitamin E and glutathione in each ambience. In all the physiological states of Rathi cattle, maximum percent variations were observed in rainy ambience. It can be concluded that among all the physiological states, calves showed maximum erythrocytic stress response during rainy ambience.